The Philippine fresh solo papaya industry price transmission elasticity, net margins and value chain analysis - Abenoja, Nadine C.; Romo, Glory D. (2009)
The price transmission elasticity (PTE) model was estimated using secondary national aggregate time-series data. Due to the unavailability of secondary data on the wholesale and retail prices of Solo papaya, the model suggests that only the price of fertilizers and the interest rate had significant linear relationships with the farmgate price. Furthermore, it was observed that only the price of fertilizer was elastic with respect to the farmgate price. The net margins and value chain analyses were carried out through case studies. The three cases that were analyzed included a farmer in Tupi, South Cotabato selling his produce to a wholesaler-retailer based in Bankerohan, Davao City; another farmer still from Tupi, South Cotabato who sells papayas to a viajero who the ships the fruits to Manila; and a contract-grower supplying a multinational agribusiness company. A fairly equitable distribution of profits among the actors in the different supply chains was observed. Certain premiums received by some actors were seen to compensate for the higher costs that they incur and the higher risks that they face. The highest farm level cost was observed at the contract-growership chain, followed by the farmer to wholesaler- retailer chain and the lowest cost was recorded in the farmer to viajero chain. Major cost items included fertilizers, farm chemicals and labor during harvest. Both the wholesaler-retailer and the incurred the most significant portion of their costs in acquiring the goods from the farm. Thus, given an efficient price transmission, the industry would benefit most from interventions directed at the farm-level. Policies and interventions that could increase farm-labor efficiency and lower the prices of fertilizers and farm chemicals would have most significant impacts.
Thesis, Undergraduate (BS Agribusiness Economics) -- University of the Philippines, Mindanao